INFLUENZA. DIAGNOSTICS, STRATEGY FOR SELECTION OF ANTI-VIRALS - N. V. Orlova (Медицинский совет, 2018)
Influenza is one of the most common diseases with a high risk of complications. Modification of influenza viruses causes epidemics and annual vaccination of the population. In the coming year, a new subtype of Michigan influenza related to the swine H1N1-influenza with a potentially severe course is expected. Antiviral drugs are essential components of a comprehensive pandemic response. Oseltamivir, zanamivir, peramivir are the new generation neuraminidase inhibitors which are considered to be the most effective drugs. A new domestic antiviral drug Nomides (oseltamivir phosphate) is the recommended drug for the treatment of influenza. It is safe and affordable for the majority of the population. Active immunization, i.e. vaccination, is the most effective method of preventing influenza.